2021
DOI: 10.3390/ijerph182111136
|View full text |Cite
|
Sign up to set email alerts
|

Family Function and Child Adjustment Difficulties in the COVID-19 Pandemic: An International Study

Abstract: To estimate specific proximal and distal effects of COVID-19-related restrictions on families on children’s adjustment problems, we conducted a six-site international study. In total, 2516 parents from Australia, China, Italy, Sweden, the United Kingdom, and the United States of America living with a young child (Mage = 5.77, SD = 1.10, range = 3 to 8 years, 47.9% female) completed an online survey between April and July 2020. The survey included the Strengths and Difficulties Questionnaire and family risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Generally, we found that the stringency of social distancing policies was negatively associated with children and adolescents’ emotional well-being and self-esteem, which is in line with previous studies that showed a negative association between the Stringency Index and mental health among adults [ 7 , 8 ] and young children aged 3–8 years [ 25 ]. Our study expands the findings from these previous studies by showing that a negative association exists between the stringency of social distancing policies and self-reported emotional well-being and self-esteem of both children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, we found that the stringency of social distancing policies was negatively associated with children and adolescents’ emotional well-being and self-esteem, which is in line with previous studies that showed a negative association between the Stringency Index and mental health among adults [ 7 , 8 ] and young children aged 3–8 years [ 25 ]. Our study expands the findings from these previous studies by showing that a negative association exists between the stringency of social distancing policies and self-reported emotional well-being and self-esteem of both children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a multi-site international study found that increased levels of household chaos were concurrently associated with higher levels of child problem behaviors, specifically, conduct problems, and to a lesser degree with emotion or peer problems (Foley et al, 2021). Cassinat et al (2021) found that higher chaos levels predicted less positive family relationships in families with adolescents.…”
Section: Environmental Factorsmentioning
confidence: 96%
“…The extant research shows that the pandemic adversely affected younger children and that the family environment is an essential factor in this change. For example, one study found an association between the impact of COVID-19 on the family unit (e.g., job loss, health worries) and child behavior problems (Foley et al, 2021). Two studies on preschool children found higher scores for behavioral problems than other pre-pandemic samples and decreased emotional and behavioral functioning between the pre-pandemic period and three weeks after lockdown (Glynn et al, 2021;Specht et al, 2021).…”
Section: Child Emotional and Behavioral Problems During The Covid-19 ...mentioning
confidence: 99%
See 2 more Smart Citations